Demand heterogeneity for index-based insurance: The case for flexible products - Ceballos, Francisco; Robles, Miguel (Elsevier, 2020)
A substantial literature has analyzed the challenges around weather index insurance, yet an important design issue has been generally overlooked. Most index insurance products have so far been characterized by a one-size-fits-all payout structure, intended for a representative farmer, at the cost of ignoring considerable heterogeneity in risk profiles. This paper provides unique evidence on the ways in which heterogeneity in farmers’ risk exposure affects their demand for insurance. We analyze a set of flexible insurance products against excess rainfall and exploit the substantial variation in insurance portfolios demanded by farmers. We explore the relevance of alternative sources of heterogeneity by extending a simple expected utility decision model and relying on structural estimation to test their significance. We find important aspects of farmer heterogeneity directly affecting their demand for insurance. We quantify the benefits of a flexible scheme by comparing farmer welfare to that achieved under alternative counterfactual insurance options.